Imitation and game approach in the teacher - philologist preparation to innovation activity (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article presents opportunities of the imitation and game in preparation of the future teacher-philologist to innovation activity; imitation and game are considered as are those, that help to realize necessity innovations in pedagogical work, to take possession of creative activity receptions, stimulate the teacher - philologist requirement for non-standard performance of professional functions.
Keywords: imitation; game; innovation approach; innovation activity; innovation